Asketisme dalam Perspektif Kristen Sebuah Pengantar - Sarjono, Haryadi; Yohanes, Heppy (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2022)
Asceticism is a religious phenomenon that is growing rapidly in religious traditions, both in revealed religion and in cultural religions, so that almost all religions have ascetic practices with different patterns. The purpose of this study is to provide knowledge to ordinary people who do not understand what asceticism is and its relation to the theology of poverty. The methodology used is a qualitative descriptive method based on the philosophy of postpositivism which is applied to the condition of natural objects where the researcher is the key instrument of data collection techniques. The results of the discussion obtained are that in the life of asceticism or spiritual practice that is carried out for believers is to struggle against worldly temptations and struggle in faith in God, while the supporting verses in the Bible, among others: 1) practice not to pay attention to worldly things (2 Timothy 2:4-5), 2). exercise to endure suffering (John 16:20-22), 3). exercise to guard the soul from all passions (1 Corinthians 6:11) and 4). training against worldly things through love for God (James 4:4).Asketisme merupakan fenomena keagamaan yang berkembang pesat dalam tradisi keagamaan, baik dalam agama wahyu maupun dalam agama-agama budaya, sehingga hampir semua agama memiliki praktek asketik dengan pola yang berbeda-beda. Tujuan penelitian ini adalah untuk memberikan pengetahuan kepada orang awam yang belum mengerti ap aitu asketisme dan kaitannya dengan teologi kemiskinan. Metodologi yang digunakan adalah metode deskriptif kualitatif yang berdasarkan pada filsafat postpositivisme yang diterapkan kepada kondisi objek yang alamiah dimana peneliti adalah sebagai instrument kunci teknik pengumpulan data.  Hasil pembahasan yang didapat adalah bahwa didalam kehidupan askesis atau latihan rohani yang dilakukan kepada orang percaya adalah berjuang melawan godaan duniawi dan berjuang dalam iman kepada Allah, sedangkan ayat yang mendukung dalam Alkitab, antara lain 1) latihan tidak mementingkan hal-hal duniawi (2 Timotius 2:4-5), 2). latihan untuk bertahan dalam penderitaan (Yohanes 16:20-22), 3). latihan untuk menjaga jiwa dari segala hawa nafsu (1 Korintus 6:11) dan 4). latihan melawan hal-hal duniawi melalui kasih kepada Allah (Yakobus 4:4).